Engineering of effective back-contact barrier of CZTSe: Nanoscale Ge solar cells – MoSe2 defects implication. (December 2019) - Lee, Sanghyun; Price, Kent J.; Saucedo, Edgardo; Giraldo, Sergio
Graphical abstract: Highlights: The effective back-contact barrier of CZTSe: nanoscale Ge is improved and characterized. The mechanism of the back-contact improvement is demonstrated with device models. The model of MoSe2 interface defect at back-contact agrees with the empirical data. The efficiency is improved up to 8.3% by including nanolayer Ge at back contact. Abstract: Using temperature-dependent measurements and device modeling, we systematically study the effective back-contact barrier of CZTSe devices to improve the property of the back-contact interface. By comparing with CZTSe devices with various nanoscale Ge configurations, CZTSe nanoscale Ge bi-layers devices show the improved power conversion efficiency by 1.1%. DC magnetron sputtering is used to fabricate CZTSe: nanolayer Ge devices. Critical device parameters are characterized to understand the impact of nanoscale Ge films on the back-contact device characteristics. Based on empirical results, modeling is performed for the influence of MoSe2 defects on the effective back-contact barrier. Analysis of experimental results of Ge bi-layers devices with the improved back-contact barrier makes a good agreement with modeling and Sentaurus TCAD simulation at the 95% confidence-level. The conversion efficiency of CZTSe: nanoscale Ge bi-layers devices is improved up to 8.3%.